Deep Crustal Faults, Shear Zones, and Magmatism in the Eastern Cordillera of Colombia: Growth of a Plateau From Teleseismic Receiver Function and Geochemical Mio‐Pliocene Volcanism Constraints. Issue 9 (10th September 2019) - Monsalve, G.; Jaramillo, J. S.; Cardona, A.; Schulte‐Pelkum, V.; Posada, G.; Valencia, V.; Poveda, E.
Abstract: The Eastern Cordillera of Colombia, in the northern Andes, is an example of an orogen in which Mesozoic basins were compressed during the Cenozoic, forming a ~2, 500‐m‐high plateau in its northern portion. Significant shortening and crustal thickening have contributed to the construction of the present topography and elevation. In this contribution, we combine the use of teleseismic receiver functions, Hf isotopes, whole‐rock geochemistry, and U‐Pb dating to help elucidate the main mechanisms that played a role in the crustal thickening and uplift of the cordillera. Receiver functions calculated for three stations on top of the plateau are consistent with the presence of thrusts that converge into major crustal interfaces at upper‐middle crustal depths; they also suggest the existence of two crustal anisotropic layers beneath the western flank of the cordillera, which we interpret to have formed as a result of shearing. In the northern portion of the plateau, in the area where two Mio‐Pliocene volcanic domes and their related deposits outcrop, a lower crustal high seismic velocity layer is suggested by the receiver functions; we propose magmatic underplating for the origin of this layer. The geochemical characteristics of the volcanic rocks in the area are consistent with partial melt in a mantle influenced by slab‐related fluids; this magma could have been added to the crust and portions of it ascended and reached the surface, experiencing assimilation and differentiation during the process. We hypothesize that this Mio‐Pliocene volcanism was related to flattening of the Nazca subducting slab. Key Points: Teleseismic receiver functions beneath the Eastern Cordillera plateau of Colombia are consistent with the presence of major crustal thrusts and shear zones where shortening may have been accommodated A high seismic speed lower crustal layer beneath two Mio‐Pliocence volcanic domes can be interpreted as magmatic underplating Mio‐Pliocene volcanism in the Eastern Cordillera of Colombia may be related to slab flattening